2018
DOI: 10.1111/ger.12363
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal disease among older people and its impact on oral health‐related quality of life

Abstract: Periodontitis did not show an association with poor OHRQL, however, a significant association between the number of teeth and poor OHRQL was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 32 publications
3
27
1
3
Order By: Relevance
“…The fact that many people in this study reported good OHRQoL may be because older people are more likely to consider minor or even severe oral health problems as less disturbing at this point in their lives because of other general health problems, and therefore express greater satisfaction with their oral health . Another explanation might be that 43% of the older people had as many as 20‐32 remaining teeth, a recent study found association between few remaining teeth and poor OHRQoL . The most frequently experienced oral problems associated with OHRQoL were painful aching in the mouth and discomfort when eating; this result is consistent with previous findings in a Norwegian study of people aged 68‐77 years …”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The fact that many people in this study reported good OHRQoL may be because older people are more likely to consider minor or even severe oral health problems as less disturbing at this point in their lives because of other general health problems, and therefore express greater satisfaction with their oral health . Another explanation might be that 43% of the older people had as many as 20‐32 remaining teeth, a recent study found association between few remaining teeth and poor OHRQoL . The most frequently experienced oral problems associated with OHRQoL were painful aching in the mouth and discomfort when eating; this result is consistent with previous findings in a Norwegian study of people aged 68‐77 years …”
Section: Discussionmentioning
confidence: 70%
“…Many factors may affect older people's OHRQoL. Previous research has shown poorer OHRQoL among people with poor self‐rated health, people dependent on support in their ADL, people with missing teeth, caries and periodontal disease, and poor self‐rated oral health . However, these relationships have not been established for older people in short‐term care.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, periodontal disease has been associated with systemic disease (e.g., diabetes, cardiovascular disease, and metabolic syndrome) [19,20]. In addition, several studies have shown that periodontitis is involved in poor oral health-related quality of life [21][22][23]. Periodontitis and tooth loss may be associated with changes in cognitive function among older adults [21].…”
Section: Discussionmentioning
confidence: 99%
“…(Horowitz & Kleinman, ; Naghibi Sistani, Virtanen, Yazdani, & Murtomaa, ). Health, QOL, oral health conditions, and oral self‐care behavior are all interrelated, but there are various factors that could be explained by models such as IBM that potentially determine whether daily oral self‐care can be correctly implemented (Dumitrescu et al, ; Kato, Abrahamsson, Wide, & Hakeberg, ; Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%